Legal and economic grounds of conclusion agreements about creation of IMF - Фіннік, С. Г. (Problems of legality, 2013)
The complex of legal and economic pre-conditions of conclusion of IMF treaty is examined in the article. It is underlined that Fund was created as organization on collaboration between the states with a purpose of adjusting of the international currency system.